Effects of Induced Moisture Loss in Chicken Embryos at Embryonic Day 18 and Post-hatch Immune Response During Salmonella enteritidis Lipopolysaccharide Challenge in Broilers - Gregorich, Jenna L.; Lilburn, Michael S.; Shanmugasundaram, Revathi (Frontiers in Physiology, 2022)
Two experiments were conducted to investigate the effects of induced moisture loss on embryonic development and the immune response following an inflammatory challenge immediately post-hatch. In Experiment I, fertile leghorn eggs (n = 100) and commercial broiler eggs (n = 300) were set at 37.5°C and moisture loss was induced in one-half of the Leghorn and broiler eggs by drilling two, 1.5 mm diameter holes. The Control eggs had 0 holes. At embryonic day (ED)18, layer and broiler eggs in the 2-holes treatment had a significant (P < 0.01) increase in moisture loss compared to the control treatment (10.1% vs. 8.2%). Similarly, at ED18, the broiler eggs with 2-holes had a significant increase (P < 0.01) in moisture loss compared with control eggs (9.9% vs. 8.4%). Thymocytes from both the leghorn (104%) and broiler (62%) embryos in the 2-holes treatment had significantly increased in vitro proliferation compared with the control embryos (P ≤ 0.05). At ED18, layer and broiler embryos in the 2-holes treatment had an approximate twofold increase in the splenic CD8+/CD4+ ratio (P ≤ 0.05) and CD4+CD25+ cells percentage in both the thymus and spleen (P ≤ 0.05). At ED18, both layer and broiler embryos from the 2-holes treatment had a significant increase in splenic IL1-β, IL-6, IL-10, and TLR-4 mRNA transcription compared to the control group (P ≤ 0.05). Experiment II was repeated with 300 fertile broiler eggs. On the day of hatch, chicks were randomly distributed into one of four treatments in a 2 (0, 2 holes) × 2 (0, 500 μg lipopolysaccharide, LPS) factorial arrangement of treatments. Chicks in the LPS groups were injected intraperitoneally with 500 μg/kg BW LPS. At 24 and 48 h post-hatch, chicks hatched from eggs with 2-holes and challenged with LPS had a significant increase (P ≤ 0.05) in thymocyte proliferation at 24 h (42%) and 48 h (37%) when compared with chicks hatched from the control (0-hole; 0 μg LPS) treatment. Chicks hatched from the 2-holes treatment and challenged with the LPS had an approximately twofold higher splenic CD8+/CD4+ ratio and 1.5 fold increase in CD4+CD25+ percentage compared to control chicks (P ≤ 0.05). In chicks hatched from the 2-holes treatment, MUC2 mRNA transcription was comparable to control chicks at 24 and 48 h in response to the LPS challenge. Our data suggest that the 2-holes treatment reprograms gene transcription to facilitate cell survival via proliferation and differentiation during an LPS inflammatory challenge.